Analisa Penyeimbang Roda Belakang Sepeda Motor 150 cc Cast Wheel Ring 17 - Saputra, Alfian Ady; Wijaya Kusuma, Ceeptadi; Hidayatulloh, Taufik (Prosiding Sains Nasional dan Teknologi, 2024)
The balance of a motorbike's wheels greatly affects the comfort of its passengers. Unbalanced wheels will cause vibrations in the vehicle body. Unbalance in a vehicle's wheels occurs when the center of mass is not in line with the axis of rotation. Therefore, it is necessary to balance the wheel so that the weight of the wheel is evenly distributed so that when it rotates the wheel can be balanced or the wheel can rotate on its axis stably. The method for solving the masses is by balancing with a balancing mass, in this case 2 balancing masses A and B using analytical methods for static and dynamic balance. The results obtained from this research are that the balancing mass for balancing vehicle wheels is obtained with a weight of Wᴀ = 1.43 N with an angle of θᴀ = 295.99˚ and a weight of Wʙ = 1.47 N with an angle of θʙ = 36.36˚ for balance. static and dynamic.